Land Arrangement for Citronella (Cymbopogon Nardus) and Arabica Coffee in the Cultivation Area in Gayo Lues District, Aceh Province Indonesia: A Land Suitability Approach - Abubakar Karim; Sugianto Sugianto; Yulia Dewi Fazlina; Muhammad Rusdi; Manfarizah Manfarizah; Hifnalisa Hifnalisa (Aceh International Journal of Science and Technology, 2020)
Gayo Lues District is known as Citronella and Arabica coffee producer in Aceh province, Indonesia. This paper aims to manage Citronella and Arabica coffee's land arrangement in the Gayo Lues District's cultivated area.  This implementation is aimed at maintaining the peculiarities of citronella products and Arabica coffee. Thus, the two commodities must be separated in terms of allocated sites.  The altitude for the area is 200-2,000 meters above sea level, consisting of ten classes, and the type of soils are Entisols, Oxisols, Inceptisols, and Ultisols. The area's slope between 0- to 40% (4 classes) was used to delineate the land units. There are 49 land units observed within the cultivated area of 160,017.17 ha.  The guidelines for land suitability classification by the Ministry of Agriculture for Citronella and Center for Coffee and Cocoa Research, Jember for Arabica coffee were utilized.   The results showed that 58,275.5 hectares of land were suitable for citronella, and 13,765.75 ha has been planted. The actual land suitability of citronella inside the area of 58,275.5 ha is suitable (S2 class) and marginally suitable (S3-class) and not suitable (N-class) with limiting factors are temperature, water availability, erosion hazard, and nutrient retention.  This land suitability can be improved by providing inputs to increase the level of suitability with temperature, water availability, and erosion hazard (slope) limiting factors. Also, 48,765.3 hectares can be developed for Arabica coffee, and 4,653.5 ha has been planted.  The actual land suitability for Arabica coffee is Suitable, Marginal Suitable, and Not Suitable, limiting the soil's physical properties (adequate soil depth), slope, and chemical properties of the soil.  Once repaired, the land's suitability becomes Suitable (S1-class) (without limiting factor), Suitable, and marginal suitable with the slope as a limiting factor. There is an area of 44,509.75 hectares of land at 200-1,400 m above sea level within the cultivation area developed with a Citronella. There is an area of 44,111.8 ha at the height of 800-2,000 m above sea level, potentially for  Arabica coffee.